Determinants of Physical Performance and Physiological Responses Duringan Official Cross-Country Marathon of Mountain-Biking (Xcm-Mtb) - Saborosa, Guilherme Pereira; Zuri, Kallil Neves; Carneiro, Túlio Junqueira; Melo, Bruno Pereira; Pussieldi, Guilherme de Azambuja; Manoel, Francisco de Assis; da Silva, Sandro Fernandes (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2024)
Introduction: The variables determinants of physical performance in cross-country marathon of mountain biking (XCM-MTB) are still unknown. Objective: We aimed to verify the training control variables and the physiological responses in an official XCM-MTB race. Material and methods: 13 athletes (11 men and 2 women; 33.3 ± 12.7 years of age) participated in this study. It was conducted during an official XCM-MTB in Brazil (route of 70 km). The heart rate (HR), altimetry, velocity, temperature, pacing, and power were obtained every 10 km travelled by the STRAVA application. Multiple linear regression analysis was performed to verify whether the variables could predict physical performance. Results: The athletes maintained constant HR elevation in the corresponding zone 80% HRmax. They also presented a variation in the pacing (F = 35.82; p < 0.001; d = 0.66) and power (F = 7.20; p < 0.001; d = 0.18) showing higher values in the last 10 km. Only pacing can be considered a predictor of the physical performance (β = 0.958; t = 7.30; p < 0.001), specifically the one at 20 km (F = 10.23; p = 0.004; R2 = 0.82). Conclusion: The study concluded that the analyzed variables are reliable for the performance control in an official XCM-MTB race. HR and power are variables that can be used to prescribe and control training, as they change according to the requirements of the race. Power can also be used as a performance predictor as it is directly influenced by terrain